Regulation of the abundance and turnover of copepod species by temperature, turbidity and habitat type in a large river basin - Perbiche-neves, Gilmar; Boxshall, Geoffrey Allan; Previattelli, Daniel; Naliato, Danilo Augusto Oliveira; Pie, Marcio Roberto; Da Rocha, Carlos Eduardo Falavigna; Nogueira, Marcos Gomes [UNESP] (Wiley, 2015)
Freshwater copepods were sampled in the La Plata River basin to identify the processes that affect beta diversity and to determine the main factors influencing their geographical distribution and patterns of endemism. Beta diversity patterns exhibited strong dissimilarity between locations; the turnover process was predominant and indicated a replacement of species along the basin. Redundancy analysis indicated the presence of two large sets of species separated geographically by a boundary zone, with several associated variables. Northern species were associated with water transparency and temperature, mean air temperature, mean air temperature during winter and minimum air temperature of coldest month, indicating that these species are not tolerant to low temperatures and are abundant in reservoirs that are common in the upper stretch of the Paraná River basin. Southern species were related with amplitude of air temperature, turbidity, total phosphorus and total suspended matter, indicating that these species are polythermic and have adapted to live in river stretches. From 20 environmental variables analyzed in our study, partial least squares analysis indicated four variables with increased retention of effects on copepod abundance: air temperature, minimum temperature of coldest month, turbidity and transparency. Because almost all of the species found in this study occurred across a wide range of habitat types, the cause of the separation between river and reservoir species could be considered to be more anthropogenic than natural, and it primarily affected species abundance. For certain members of the northern group of copepod species, distribution was dependent on high temperatures, whereas the distribution of the southern group indicated that the species were polythermic.
Keywords: Crustacea; Diaptomidae; Endemism; La Plata River basin; South America